GESTÃO SOCIAL E CIDADANIA: PROJETO DE EXTENSÃO INTEGRADO À PESQUISA E AO ENSINO - Allebrandt, Sergio L.; Prediger, Reneo P.; Schneider, Leandro; Martins, Carlos V. d. M.; Wuaden, Fernanda; Dutra, Clarissa; Dallepiane, Sabrina (Salão do Conhecimento, 2013)
Resumo